Indonesian Islamic Banks and Financial Stability: An Empirical Analysis - Firna Hayyu Nindya Maritsa; Agus Widarjono (EkBis: Jurnal Ekonomi dan Bisnis, 2021)
Islamic banking in Indonesia is very vulnerable to volatility in their business processes due to its small market share. Compared to conventional banks, seen from their financial performance, Islamic banks have a worse performance because of lower profit (ROA). This study examines the stability of Islamic banking in Indonesia. Stability is measured using the Z Score. The data in this study are aggregate data for Islamic commercial banks. The data used are monthly data from January 2015 to December 2019. This study uses the ARDL (Autoregressive Distributed Lag) method. The results of this study are that all independent variables OER, NPF, inflation, IPI, exchange rates have an effect on the stability of Islamic banking, except FDR. Lower efficiency and problematic financing increases the stability of Islamic banking. Meanwhile, macroeconomic factors, inflation and exchange rates, have a negative effect on the stability of Islamic banking. The economic downturn due to inflation and rupiah depreciation will increase the instability of Islamic banks.